Promising Protection, Producing Exposure: AI Ethics and Mobile Communication Regulation in Indonesia - Floranita, Rustini; Darius, Diamitra; Irwansyah, Irwansyah (Syntax Literate, 2026)
This study examines the paradoxical nature of Indonesia's governance of mobile artificial intelligence (AI), where regulatory discourse promises ethical protection yet simultaneously produces new forms of social exposure. Through qualitative analysis of key policy documents, ethics guidelines, and stakeholder commentary, this research investigates how state, industry, and academic actors frame the promises and risks of mobile-AI systems. The analysis is guided by communication rights theory, the Social Construction of Technology (SCOT), and communication ecology perspectives. It identifies three dominant patterns: first, Indonesia’s governance relies heavily on aspirational yet non-binding soft-law instruments, limiting accountability; second, national and industrial narratives predominantly position AI as an engine for economic growth under the Golden Indonesia 2045 vision, often obscuring structural risks like algorithmic bias and data exploitation; and third, regulatory frameworks tend to overlook vulnerable groups—including low-wage workers, women, and rural communities—whose mobile communication practices are disproportionately exposed to harm. The article argues that Indonesia's current approach creates a critical gap between policy intent and lived experience. It concludes that a stronger, communication-rights-based regulatory framework is essential to ensure equitable and accountable mobile-AI futures in Indonesian society.